Non-Invasive Screening of Hormonal and Metabolic Risk for Type 2 Diabetes in Adolescents: A Cross-Sectional Study - Erlena, Erlena; Sopiatun, Siti; Nurdiansyah, Tubagus Erwin (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Type 2 diabetes (T2D) among adolescents is increasingly linked to early-onset obesity, hormonal dysregulation, and sedentary lifestyles. Early detection through non-invasive methods is crucial for preventing long-term complications. However, few studies have examined the combined influence of hormonal and lifestyle-related factors in obese adolescents. Objective: To identify key predictors of metabolic risk for T2D in obese adolescents using non-invasive screening approaches. Methods: A cross-sectional study was conducted involving obese adolescents aged 13–15 years. Non-invasive assessments included anthropometric measurements, dietary and physical activity questionnaires, and a hormonal imbalance questionnaire. Additional potential confounders considered were the participants sex and age. Multivariate logistic regression was used to analyses the association between risk factors and metabolic risk, with hormonal imbalance as a primary predictor. The model was adjusted for obesity severity, parental history of diabetes, physical activity, and dietary patterns. Results: Five significant predictors were identified: hormonal imbalance, obesity severity, parental history of diabetes, low physical activity, and poor dietary patterns. Hormonal imbalance was evaluated through a self-administered questionnaire., was the strongest predictor (p < 0.05). Conclusion: This study highlights the need for early screening strategies targeting hormonal and lifestyle factors. Non-invasive methods can be used to identify adolescents at risk for T2D.